2016
DOI: 10.1093/hmg/ddw118
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandin vivorescue of aberrant splicing inCEP290-associated LCA by antisense oligonucleotide delivery

Abstract: Leber congenital amaurosis (LCA) is a severe disorder resulting in visual impairment usually starting in the first year of life. The most frequent genetic cause of LCA is an intronic mutation in CEP290 (c.2991 + 1655A > G) that creates a cryptic splice donor site resulting in the insertion of a pseudoexon (exon X) into CEP290 mRNA. Previously, we showed that naked antisense oligonucleotides (AONs) effectively restored normal CEP290 splicing in patient-derived lymphoblastoid cells. We here explore the therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
126
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(134 citation statements)
references
References 55 publications
6
126
2
Order By: Relevance
“…Similarly, naked AONs and adeno-associated virus-packaged AONs were administered to a humanized mouse model ( Cep290 lca/lca ) that contains intron 26 of the human CEP290 gene carrying the c.2991+1655A>G mutation. Delivery by intraocular injection caused a statistically significant reduction of aberrantly spliced Cep290 up to 1 month after injection, without compromising the retinal structure 19 . However, humanized Cep290 lca/lca mouse fails to recapitulate the human clinical features, making it impossible to understand the actual impact of AON-directed restoration of wild type Cep290 transcript on the retinal phenotype 1820 .…”
Section: Manipulation Of Splicing For Therapeutic Benefitmentioning
confidence: 89%
“…Similarly, naked AONs and adeno-associated virus-packaged AONs were administered to a humanized mouse model ( Cep290 lca/lca ) that contains intron 26 of the human CEP290 gene carrying the c.2991+1655A>G mutation. Delivery by intraocular injection caused a statistically significant reduction of aberrantly spliced Cep290 up to 1 month after injection, without compromising the retinal structure 19 . However, humanized Cep290 lca/lca mouse fails to recapitulate the human clinical features, making it impossible to understand the actual impact of AON-directed restoration of wild type Cep290 transcript on the retinal phenotype 1820 .…”
Section: Manipulation Of Splicing For Therapeutic Benefitmentioning
confidence: 89%
“…The dual vector approach has yet to be tested successfully for the delivery of CEP290 . In lieu of gene replacement, antisense oligonucleotides (AONs) and CRISPR/Cas9 genome editing have shown promise for correcting aberrant splicing of a deep intronic mutation (c.2991 + 1655A > G) (Garanto et al, 2016; Gérard et al, 2015; Ruan et al, 2017), the most common CEP290 -LCA mutation generating a cryptic splice donor site (den Hollander et al, 2006). However, functional improvement has not been demonstrated in vivo by these approaches due to the lack of animal models that faithfully mimic the aberrant splicing in photoreceptors (Garanto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This cryptic exon harbors a premature termination codon that renders the CEP290 protein non-functional. Previous reports characterize the effects of this mutation and others on features of primary cilia formation and CEP290 splicing in patient-derived fibroblasts (7,8). Since this mutation is associated with an ocular-specific disease phenotype, the authors build upon previous investigations by reprogramming dermal fibroblasts derived from a homozygous donor to an induced pluripotent stem cell (iPSC) state followed by differentiation toward a cellular fate representative of retinal precursors within threedimensional optic cups.…”
mentioning
confidence: 99%
“…Alternative approaches that selectively manipulate the endogenous CEP290 DNA using genome editing or mRNA sequence manipulations may provide an attractive means to bypass the drawback of current gene augmentation strategies using AAV gene delivery of large cDNAs. With respect to the c.2991 + 1665A>G mutation, previous reporting highlights the efficacy and potential therapeutic benefit of antisense oligonucleotides (ASOs) in selectively masking this cryptic splice mutation and restoring the correct CEP290 reading frame (8). Using AAV-mediated expression of ASOs, Garanato et al (8) demonstrated functional restoration of CEP290 pre-mRNA splicing, wild-type protein levels, and ciliogenesis in patient-derived fibroblasts.…”
mentioning
confidence: 99%
See 1 more Smart Citation